A retrospective comparative study of the clinical and radiological outcomes of intertrochanteric fractures treated with proximal femoral nail antirotation (PFN-A) and INTERTAN nail - Hasan Orkun Varmış; Mehmet Yiğit Gökmen; İsmet Tan (PLoS ONE, 2025)
Background This study aimed to analyze the files of patients treated using PFN-A or INTERTAN intramedullary nails to reveal additional superiorities or disadvantageous factors for selecting the better intramedullary fixation method in patients presenting with intertrochanteric femur fractures. Methods In this retrospective study, the files of the patients who were operated on for intertrochanteric femur fractures using intramedullary fixation methods between September 2010 and June 2015 in the Orthopedics and Traumatology Clinic, Çukurova University Faculty of Medicine, were reviewed. The data including age, gender, chronic diseases, causes of fractures, fracture classification based on Arbeitsgemeinschaft für Osteosynthesefragen (AO), the nail type (long or short), the interval between trauma and surgery, duration of anesthesia and surgery, hospitalization duration, amount of blood transfusion, the Tip-Apex Distance (TAD) in postoperative radiographs, functional outcomes according to Harris Hip Score (HHS) and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), postoperative complications, need for revision, and mortality was noted. The data of the follow-up visits included physical examination findings in addition to the radiological assessment findings obtained using X-ray imaging involving the evaluation of the union in terms of the presence of infection, loss of reduction, implant failure, avascular necrosis, additional signs related to poor union formation, and the position data of the lag screw placement point according to Cleveland and Bosworth Quadrants. Results The records showed that 194 files were available for analysis. The mean age of the patients included in the study was 70.9±16.4 years; 100 patients (51.5%) were male, and 94 (48.5%) were female. There were 76 patients (39%) in the PFN-A group and 118 patients (61%) in the INTERTAN group. Analysis of the mean Harris Hip Scores in both nail groups showed that only the mean scores at the 1st follow-up were statistically significantly different (P = 0.025). Conclusion In conclusion, comparing the two nail types in terms of complication rates and clinical data, neither nail has proven superior to the other. Moreover, the temporary difference in the first follow-up HHS scores should not be considered an indicator of the overall functional outcome because long-term follow-up HHS scores did not differ.